Economics for Environmental Studies A Strategic Guide to Micro- and Macroeconomics - Endres, Alfred. (Springer Texts in Business and Economics, 2012)
An understanding of fundamental economic concepts is essential for students in environmental studies programs around the world. The present textbook addresses their needs, providing a concise introduction to micro- and macroeconomics and demonstrating how these economic tools and approaches can be used to analyze environmental issues. Written in an accessible style without compromising depth of the analysis, central issues in the public policy debate on environmental problems and environmental policy are discussed and analyzed from an economics perspective. The book is meant both as an introductory text for undergraduate students in environmental sciences without a background in economics, and as a companion for economists interested in a presentation of the micro and macro foundations of environmental  economics, in a nutshell.